(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article discusses the psychological changes of primary school students during the period of schooling, the role and responsibility of teachers, parents and relevant state bodies in their systemic formation, as well as psychological changes in children. the ability to respond to changes in the environment and society.